5+3(x-2)=-1

Simple and best practice solution for 5+3(x-2)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+3(x-2)=-1 equation:


Simplifying
5 + 3(x + -2) = -1

Reorder the terms:
5 + 3(-2 + x) = -1
5 + (-2 * 3 + x * 3) = -1
5 + (-6 + 3x) = -1

Combine like terms: 5 + -6 = -1
-1 + 3x = -1

Add '1' to each side of the equation.
-1 + 1 + 3x = -1 + 1

Combine like terms: -1 + 1 = 0
0 + 3x = -1 + 1
3x = -1 + 1

Combine like terms: -1 + 1 = 0
3x = 0

Solving
3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '3'.
x = 0

Simplifying
x = 0

See similar equations:

| 2/3(3x+5)=-24 | | 4/9=-y/3 | | 9x+1=10x+12 | | 5x-4x(x-3)=17 | | -8.1=-13.4-1.4x | | 2e^6x+e^3x-28=0 | | 10x+29=6x+121 | | -9/8t=7/4 | | 2x=n(a+y) | | 4x+8x-2=20-15 | | 5(4-k)=10 | | 5-b=2x | | 16=5(x-1)-(x-9) | | (6x-6)+(5x-2)+x= | | 6(2x-2)=2(6+5) | | 6x=458.40 | | v-2.72=3.63 | | X+sqrt(x)=0 | | 14(t-6)+4t=6(3t+4)-11 | | 12/5=6x | | 3v-15=36 | | 9p-7p= | | 3(a-5)=-10 | | (1-1/n)(1-2/n) | | 0.25x^2-8x+64=0 | | 4y+4y=7y-1 | | 5(x+10)=40 | | 5(x-4)=3x-7 | | 36.90=9 | | x-3=-27 | | 9p-7p+4p-6p= | | 3x/4=9/2 |

Equations solver categories